Review of fetal choroid plexus cysts: A cross-sectional study on 9244 pregnant women - Aktürk, Erhan; Güler, Aşkın Evren (Journal of Surgery and Medicine, 2020)
Aim: It was revealed in many studies conducted on unselected populations that the size, bilaterality and number of choroid plexus cysts (CPCs) are correlated with various degrees of aneuploidy risk. This article deals with the natural history and significance of numbers, sizes and bilaterality of CPCs in a selected population. Methods: This cross-sectional study was conducted on 9244 pregnant women attending to our department between March 2014 and March 2018. After exclusion criteria was applied, 87 patients with isolated CPCs remained. All records of the patients were screened and needed data were recorded. Results: A total of 9244 prenatal sonographies had been performed during this period. Isolated CPC was detected in 87 fetuses. CPCs were visualized unilaterally in 83 cases (95.4%) and bilaterally in 4 cases (4.6%). Among 83 unilateral cases, 45 had left sided (51.7%) and 38 had right sided CPCs (43.7%). The size of the cysts ranged between 3 mm to 5.1 mm with an average of 3.51 (0.06) mm. Double tests (n=24) and quadruple tests (n=63) had 2 and 5 abnormal results, respectively. All had normal karyotypes. Four samples were dropped out due to premature rupture of membranes (n=2) and intrauterine fetal death (n=2). It was found that the outcomes of all remaining fetuses (n=83) were normal and no anomalies were seen until birth. Conclusion: Multiple CPCs in a single choroid plexus or bilaterality were not associated with abnormal fetal karyotype and therefore we think that isolated CPCs has a good prognosis.